Britain's forgotten minister of adult education: Arthur Creech Jones and a socialist strategy for development and democracy in Africa - John Holford (Adult Education Research Conference, 1995)
Creech Jones is the only major British Minister who has made adult education central to his policies. His outstanding contribution to adult education policy and practice has been unjustly ignored in adult education literature.